You and me together : moms, dads, and kids around the world - Kerley, Barbara (Washington, D.C. : National Geographic, 2010)
Presents a collection of full-color photographs depicting mothers, fathers, and children around the world and the things they share together.
Wilson's Children, October 2006
Notable/Best Books (A.L.A.), January 2006
School Library Journal, April 2005
Library Media Connection starred, March 2005
Booklist, April 2005
Horn Book, October 2005
Keywords: Parent and child -- Juvenile literature; Parent and child; Parent-child relationship